Characteristics and Predictors of Venous Thromboembolism Among Lymphoma Patients Undergoing Chemotherapy: A Cohort Study in China - Chen, Yue; Lei, Haike; Wang, Wei; Zhu, Jie; Zeng, Chensi; Lu, Zhuo; Li, Luchun; Li, Dairong; Long, Bo; Liu, Haixia (Frontiers in Pharmacology, 2022)
Background: Venous thromboembolism (VTE) is a potential complication among lymphoma patients. We evaluated the incidence rate and predictors of VTE in lymphoma patients undergoing chemotherapy. Methods: The present study retrospectively studied 1,069 patients with lymphoma who were treated with chemotherapy from 2018 to 2020. We investigated clinical predictors of VTE among all patients. The follow-up results were obtained via telephone communication and from inpatient and outpatient records. Results: A total of 1,069 patients underwent chemotherapy for lymphoma. During a mean follow-up of 23.1 months, 52 (4.9%) patients developed VTE. According to a multivariate analysis, the five variables found to be independently associated with VTE were male sex (HR 2.273, 95% CI 1.197–4.316, p = 0.012), age >64-years-old (HR 2.256, 95% CI 1.017–5.005, p = 0.045), the number of cycles of chemotherapy (HR 4.579, 95% CI 1.173–17.883, p = 0.029), platelet count ≥350 × 109/L (HR 2.533, 95% CI 1.187–5.406, p = 0.016), and D-dimer >0.5 mg/L (HR 4.367, 95% CI 2.124–8.981, p < 0.001). Conclusion: This population-based study confirms the risk factors for VTE among patients with lymphoma who underwent chemotherapy and confirms that targeted thromboprophylaxis may reduce the burden of VTE in this population.